Comparación del Autoconcepto en Adolescentes que Conviven y No Conviven con su Padre Biológico en Hatonuevo, la Guajira (2024)
The present study is framed under the problems associated with self-concept in adolescents based on the variable associated with whether or not they live with the biological father, which is why the research aimed to compare the self-concept of adolescents who live and do not live with his biological parents from a neighborhood in the Municipality of Hatonuevo, La Guajira. For the purposes of the above, the study was developed under a mixed approach, of a quantitative type with a non-experimental design and from the qualitative framework it had a non-experimental design, likewise, it had the participation of 60 subjects to whom it was applied a sociodemographic characterization instrument, the EVA 42 to measure self-concept, and a structured interview applied to two participants